THE APPLICATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL, AND MEDIUM ENTITIES (SAK-EMKM) IN THE PROCESS OF MAKING REPORTS FINANCE FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (CASE STUDY IN MSMES ABADI CELL SRIBAWONO) - Sandy Gunawan; Afrizal Nilwan (ZILLZELL MEDIA PRIMA, 2025)
MSMEs at this time have a great influence on the country's economic development, especially in Indonesia, but many MSME actors have not implemented SAK EMKM in compiling financial statements. The purpose of the study is to find out whether Abadi Cell MSMEs apply SAK EMKM in the preparation of reports or not and to design the preparation of financial statements so that they are in accordance with SAK EMKM. The method used is qualitative case studies by means of data collection, namely by conducting interviews, observations, and documentation. The results of the research conducted that Abadi Cell did not apply SAK EMKM in compiling financial statements so that the researcher designed the preparation of financial statements based on SAK EMKM by producing profit and loss statements, financial position statements, notes on financial statements (CALK) and the researcher encouraged Abadi Cell to continue to prepare SAK EMKM financial statements.